The effects of e-quality on tourist experience and tourist satisfaction in Malaysia / Sajjad Tarzaban - Tarzaban, Sajjad (2019)
This study investigates the correlation of Malaysia’s economy-tourism business with internet and e-commerce, and their influence on tourists’ satisfaction. This research study explores travellers’ adoption of e-travel services in the context of Malaysian travel services. The key objective is to identify the profile of e-commerce competitive advantages, Internet technology, electronic travel service quality (E-QUAL), and tourist experience on Malaysian tourist satisfaction adoption for e-travel services. Since Malaysia is benefiting of its internet technology and e-travel services then tourist destination in Malaysia could be one of the famous destinations in South-East Asia. This research aims to assess the effects of Internet technology acceptance, e-commerce competitive advantages, e-travel services, and tourist experience on tourist satisfaction in Malaysia. It focuses on the relationship between two individual variables of e-commerce with four items (product, brand, service, and price) and internet technology with two dimensions (usefulness and easiness) on tourist satisfaction (TS). Furthermore, two mediating variables, E-QUAL with five items (information quality, security, website functionality, customer relationship and responsiveness), and tourist experience (TEX) with three dimensions (arousal, education and escapist) are analysed.